Work-related rumination as a mediator between hindrance demands and sleep quality - Janina Janurek; Nina M. Junker; Sascha Abdel~Hadi; Andreas Mojzisch; Jan A. Häusser (Journal of Occupational and Organizational Psychology, 2024)
Job demands can negatively affect sleep. However, previous studies have provided inconclusive results regarding the mediating role of work-related rumination in this relationship. Integrating prolonged activation theory with the challenge-hindrance framework, we hypothesized that – on a day level – hindrance demands, but not challenge demands, are negatively associated with sleep quality and sleep duration via work-related rumination. We tested this assumption in a 14-day ambulatory assessment study with a sample of employees ( N 0.167em=0.167em175). As predicted, we found that only hindrance demands, but not challenge demands, are related to sleep quality via work-related rumination. No relationships with sleep duration were found for any type of job demands.
Keywords: 650; challenge demands; hindrance demands; job demands; perseverative cognition; rumination; sleep